Inclusive developments through socio-economic indicators : new theoretical and empirical insights - Das, Ramesh Chandra (Emerald Publishing Limited, 2023)
In line with rapid world economic growth, globalization has led to a decrease in global income inequality, according to the World Bank. However, in some contexts, income disparity continues to rise, proving that a variety of factors can determine wealth and income across different countries and regions. Social indicators in particular play a serious role in the development of such inequalities, though their impacts have previously been of little interest to economic scholars. Proposing issues that hinder equal development, Inclusive Developments through Socio-economic Indicators: New Theoretical and Empirical Insights focuses upon the roles of different socio-economic indicators in explaining the convergence or inclusiveness of income across groups of varying wealth as well as within larger economies. Employing both theoretical and empirical thinking from across the world, contributors also provide thought-provoking solutions to pervasive social, global and economic issues, including sustainable development. Beneficial for researchers, economists and policy makers, Inclusive Developments through Socio-economic Indicators: New Theoretical and Empirical Insights encapsulates the roles of different socio-economic indicators in justifying the convergence of income and wealth at a global level.